(-)-Epigallocatechin Gallate Reduces Platelet-Derived Growth Factor-BB-Stimulated Interleukin-6 Synthesis in Osteoblasts: Suppression of SAPK/JNK - Shinji Takai; Rie Matsushima-Nishiwaki; Seiji Adachi; Hideo Natsume; Chiho Minamitani; Jun Mizutani; Takanobu Otsuka; Haruhiko Tokuda; Osamu Kozawa (Mediators of Inflammation)
We previously showed that the mitogen-activated protein (MAP) kinase superfamily, p44/p42 MAP kinase, p38 MAP kinase, and stress-activated protein kinase (SAPK)/c-Jun N-terminal (JNK), positively plays a part in the platelet-derived growth factor-BB- (PDGF-BB-) stimulated synthesis of interleukin-6 (IL-6), a potent bone resorptive agent, in osteoblast-like MC3T3-E1 cells while Akt and p70 S6 kinase negatively regulates the synthesis. In the present study, we investigated whether (-)-epigallocatechin gallate (EGCG), one of the major green tea flavonoids, affects the synthesis of IL-6 in these cells and the mechanism. EGCG significantly reduced the IL-6 synthesis and IL-6 mRNA expression stimulated by PDGF-BB, EGCG reduced the PDGF-BB-stimulated IL-6 synthesis also in primary-cultured osteoblasts. EGCG had no effect on the levels of osteocalcin and osteoprotegerin in MC3T3-E1 cells. The PDGF-BB-induced autophosphorylation of PDGF receptor β was not suppressed by EGCG. The PDGF-BB-induced phosphorylation of p44/p42 MAP kinase and p38 MAP kinase was not affected by EGCG. On the other hand, EGCG markedly suppressed the PDGF-BB-induced phosphorylation of SAPK/JNK. Finally, the PDGF-BB-induced phosphorylation of Akt and p70 S6 kinase was not affected by EGCG. These results strongly suggest that EGCG inhibits the PDGF-BB-stimulated synthesis of IL-6 via suppression of SAPK/JNK pathway in osteoblasts.